PENERAPAN FINITE STATE AUTOMATA TERHADAPPROSES PENDAFTARAN PRAKTIKUM PADA JURUSAN TEKNIK INFORMATIKA - Muhammad Oky Risaldi; Febrian Ray Gere SW; Indra Rajsya; Heru Sutejo (CV Edujavare Publishing, 2024)
Finite State Automata (FSA) is an abstract machine derived from formal language theory, widely applied in computing for validating structured processes. This study explores the application of FSA in automating the practicum registration system for Informatics Engineering students at Universitas Sepuluh Nopember Papua. The registration process previously encountered challenges, such as schedule conflicts between practicum and lectures, overcapacity of classes, and data input errors, which hindered academic activities. To address these issues, FSA was employed to ensure automated validation at each step of the registration process. The system operates through a series of states, beginning from course selection to practicum schedule validation, shift assignment, and confirmation. The FSA model designed consists of five states: initial state, course selection state, validation state, shift selection state, and confirmation state. If an error occurs, the system provides feedback and redirects students to correct their input. Using a structured approach, this model prevents scheduling conflicts and ensures data consistency. The methodology integrates observation, interviews, and literature reviews to identify problems and design the FSA model. The system was implemented using a programming framework, validated through simulations using both valid and invalid registration data. Results demonstrated that the system effectively minimized errors, improved the accuracy of practicum registration, and streamlined the process. In conclusion, the implementation of FSA significantly enhances the efficiency and organization of practicum registration, providing automated feedback and ensuring students successfully complete their registrations without conflicts or input errors.